Improving Student Mathematical Understanding through the Implementation of the STAD Method at STIKOM Tunas Bangsa - Zulaini Masruro Nasution; Ika Okta Kirana; Fitri Anggraini; Nani Hidayati; Fitri Rizki (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2025)
One of the factors for the low mathematical understanding of students is the inappropriate learning method. The selection of the STAD method is believed to be able to improve students' mathematical understanding. This research uses a quantitative approach (pre-experiment). This study aims to determine the difference in students' mathematical understanding before and after using the STAD method. The research population consisted of STIKOM Tunas Bangsa students majoring in Information Systems in the 2023-2024 academic year, with 8 classes, and the sample was drawn from class 23S01. Quantitative data analysis using SPSS 25, namely paired sample t-test. The results showed that the correlation value was 0.714, indicating a strong and significant correlation between initial understanding and final understanding. Based on the mean value of initial understanding (pretest) with a value of 70.83, lower than the mean final understanding (Post-test) after using the STAD method of 79.44. The sig. A value of 0.00 or smaller than 0.05 states that mathematical understanding after using the STAD method is higher than before using the STAD method. Thus, it can be concluded that there is a significant and strong increase in mathematical understanding after using the STAD-type cooperative method in higher education, one of which is for STIKOM Tunas Bangsa students